2012
DOI: 10.1021/cm300293b
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Monodispersed Cobalt Nanoparticles Filled into Multiwalled Carbon Nanotubes

Abstract: Magnetic cobalt-based nanoparticles (NPs) with homogeneous size were selectively cast inside the channel of multiwalled carbon nanotubes (CNTs). The proposed synthesis method allows for filling only the CNTs channel with an unprecedented high density. The CNTs act as “nanoreactors” and provide protection against oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…In the same vein, Liu et al. very recently demonstrated the possibility to use amino‐functionalized Co and Fe oxides MNPs@CNTs, produced from the stearate precursors method developed earlier by the same team66 (Figure 5), for magnetic manipulation of cells in‐vitro 102. They were able to show that, depending on the direction and the frequency of the field applied, their hybrids can be either taken up by cells, drive cell motion, or act as a remote “nano‐stirring bar” in the biological media.…”
Section: Applications Of Magnetically Active Carbon Nanotubesmentioning
confidence: 95%
See 3 more Smart Citations
“…In the same vein, Liu et al. very recently demonstrated the possibility to use amino‐functionalized Co and Fe oxides MNPs@CNTs, produced from the stearate precursors method developed earlier by the same team66 (Figure 5), for magnetic manipulation of cells in‐vitro 102. They were able to show that, depending on the direction and the frequency of the field applied, their hybrids can be either taken up by cells, drive cell motion, or act as a remote “nano‐stirring bar” in the biological media.…”
Section: Applications Of Magnetically Active Carbon Nanotubesmentioning
confidence: 95%
“…for encapsulating monodisperse 50 nm‐diameter MNPs of Co (Figure 5). 66 For this purpose, cobalt stearate impregnated in open‐tips CNTs was used as a precursor for the thermal transformation reaction 32a. 69 Reference thermal reduction experiments in the absence of the carbon frameworks showed the limited formation of NPs thus confirming the templating role exerted by the nanotube cavity on the nanoparticle synthesis.…”
Section: Preparation Of Magnetically Active Carbon Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Raman I D /I G ratio for the monoliths (Table 2) lower than that found prior to consolidation (Table 1), which could reflect the elimination of surface defects and formational defects in the CNT outer walls by a thermal annealing effect during SPS. Indeed, other authors [41,42,46] have reported that oxygen functional groups can be selectively removed from a CNT surface and formational defects can anneal out at relatively low temperatures, below 1600°C, whereas microstructural defects within the MWCNT structure require subsequent annealing at much higher temperatures (typically above 3000°C). The trend, however, is that the I D /I G ratio increases upon the increase in temperature and this density (Fig.…”
Section: Carbon Nanotube Monolithsmentioning
confidence: 99%